Açaí: expansão comercial e cadeia produtiva - SILVA, Deybson Adriano Patrício da (2019)
Açaí has significant cultural and economic importance in the Amazon, and in recent years the external visibility of the fruit has been increasing through extraction by traditional families for own consumption and small commercialization, as well as industrial production. With increasing demand for consumption, the açaí has aroused commercial interest and other market spheres, and started to have a more intense and planned crop to possibly meet this demand. In this expectation the work is oriented to understand the dynamics of the açaí productive chain in the lower and upper economy circuits, from the systematization and empirical cut of the municipality of Belém. Its profitability is considerably high as regards the economic return to the state of Pará; the circulation of the local açaí has formal and informal market bias for the generation of income and livelihood of families in the social space, and increasing emergence of export companies and their disparities of economic return to the state in the production of açaí. Obstacles in the production of açaí demand, required government investments in the lower cycle, are addressed in the work, as well as the nutritional value of açaí as external consumer interest. The work builds on the argumentation from bibliographical summaries and interviews with actors connected to the chain in different positions, besides the theoretical approach of authors who discuss the theme. The results point to a significant and growing açaí expansion in the local, national and international market, with values and analysis of expressive data that speculate a tendency of this economic growth.